Nurses' perception of troubled conscience in intensive care units: a qualitative study - Mohammad Ali Cheraghi; Maryam Esmaeili; Monir Mazaheri; Fatemeh Abdi; Kurosh jodaki (BMC, 2024)
Abstract Background Troubled conscience results from the lack of attention to the voice of conscience. Regarding the fact that ICU healthcare workers are constantly faced with stressful and challenging situations, they often experience a troubled conscience. Aim This study aimed to explain the factors leading to troubled conscience and identify the consequences of troubled conscience among ICU nurses. Methods Qualitative content analysis was used to answer the research question. A total of 18 ICU nurses were selected to participate in this study using purposive sampling. Data were collected using face-to-face, semi-structured interviews. Findings Four categories of "carelessness", "contextual challenges", "non-supportive and unpredictable structure" and "whirlpool of troubled conscience" were shown to constitute the main causes of troubled conscience among ICU nurses. Conclusion Troubled conscience negatively impacts nurses and is associated with psychological/behavioral changes among them. The identification and explanation of troubled conscience help healthcare providers to confront it and manage its causes.